Addition of five orchid species to the flora of Bhutan - Gyeltshen, Phub; Rabgay, Kinley; Phuentsho; Tobgay, Kezang; Namgyel, Pema (Lankesteriana: International Journal on Orchidology, 2024)
Bhutan, situated in the eastern part of the Himalaya Biodiversity Hotspot, is renowned for its rich flora and fauna. This biodiversity is attributed to the country’s multiple biogeographic origins, diverse topo- graphy, ecological complexity, and varied climatic and soil conditions. However, much of the flora remains under-collected, with many taxa yet to be discovered. From June 2022 to March 2024, floristic studies were conducted in Bhutan, leading to the discovery of five orchid species not previously recorded in the country: Bulbophyllum crabro, B. rigidum, Cymbidium tortisepalum var. longibracteatum, Galeola cathcartii, and Liparis kumokiri. These species are scientifically documented for the first time in Bhutan. Detailed descriptions, type information, updated global distribution, ecology, and colour plates of the recorded species are provided.